PEMETAAN POTENSI EKOWISATA DI DESA TANJUNG BELIT DAN DESA LUBUK BIGAU KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR PROVINSI RIAU - Abdullah Rinaldi Zen; Emy Sadjati; M Ikhwan (Fakultas Pertanian, Universitas Riau, 2017)
Tanjung Belit Village and Lubuk Bigau Village, Kampar Kiri Hulu Subdistrict, Kampar District have a lot of tourism potential that can increase regional economy and income. This study utilized geographic information system technology (GIS) to map potential natural tourism areas because they are considered more effective and efficient. Geographic Information System is one of the development of information systems that combine information systems with geography, which is widely used to plan, analyze, and make decisions. The purpose of this study was to create inventory and map potential natural tourism objects. This study used survey method or direct visits to research objects. The data sources used are primary and secondary data obtained from observations and taking coordinates and tracks in the field, as well as a map of the earth's appearance in Kampar left upstream. Data were analyzed using descriptive analysis methods. The theoretical basis used is the tally sheet guideline for analysis of objects and natural tourist attractions of the Directorate General of PHKA 2003 and ArcGis 10.1 software. Based on the data analysis, the results of this study were in the form of information on 5 potential natural tourism objects, namely: (1) batang kapas waterfall of ± 150 m; (2) batang kapas waterfall of ± 50m; (3) batu dinding waterfall one; (4) batu dinding waterfall two and (5) air seluncur and potential maps containing information about potential natural tourism objects.